STORY FORMULA AND FEMINIST IDEOLOGY IN EAT PRAY LOVE NOVEL - Dyah Kristyowati (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
Eat Pray Love novel by Elizabeth Gilberth tells the story of a woman's journey to herself in three countries over a period of one year. There are also countries visited are Italy, India and Indonesia. Her visit to the three countries was in order to find a balance in her life. This is evident from the interaction between the characters and the conflicts contained in the novel. The journey to the Italian state to explore the arts of fun, deepen the art of meditation and devotion in the country of India and balance the two in Bali Indonesia. Feminist ideology is seen in the main character of the novel as well as some other female figures mentioned in Elizabeth's novel taking the greatest step in her life to end her marriage and find her own life and happiness as a woman. In this novel also told a figure Indian girl named Tulsi who chose to continue his education in the middle of an environment that opposed women to have  high education.  Keywords: story formula; feminist ideology.